2005
DOI: 10.1159/000089756
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Amino Acid Positions Crucial for IgE-Binding Epitopes of the Major Apple <i>(Malus domestica)</i> Allergen, Mal d 1

Abstract: Background: Individual amino acid residues of the major birch pollen allergen, Bet v 1, have been identified to be crucial for IgE recognition. The objective of the present study was to evaluate whether this concept was applicable for the Bet v 1-homologous apple allergen, Mal d 1. Methods: A Mal d 1 five-point mutant was produced by PCR techniques, cloned into pMW 172 and expressed in Escherichia coli BL21(DE3) cells. To evaluate the allergenic properties of the engineered protein compared to Mal d 1 wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 91 publications
6
62
0
1
Order By: Relevance
“…Moreover, site-directed mutagenesis has been used successively to produce low IgE-reactive recombinant forms of the popular allergens such as major apple allergen Mal d 1 and birch pollen allergen Bet v 1. [24][25][26] These results have shown that replacement of only a few key amino acids within an allergen molecule can significantly reduce the human IgE reactivity of these allergenic proteins. Modified recombinant allergens exhibiting reduced allergenicity seem to decrease the risk of symptoms and to be useful for immunotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, site-directed mutagenesis has been used successively to produce low IgE-reactive recombinant forms of the popular allergens such as major apple allergen Mal d 1 and birch pollen allergen Bet v 1. [24][25][26] These results have shown that replacement of only a few key amino acids within an allergen molecule can significantly reduce the human IgE reactivity of these allergenic proteins. Modified recombinant allergens exhibiting reduced allergenicity seem to decrease the risk of symptoms and to be useful for immunotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Site-specific mutagenesis can be a valid tool to identify the essential role of single amino acid substitution in immunological response [9,17]. With this method, the region 38-55 of Par j 2 has been shown to be the most powerful for eliciting allergenic reaction in the serum of atopic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The epitope must be classified as discontinuous. However, residues 42-52 (including the alleged "P-loop like" region 46-51 of the Bet v 1 sequence) constitute 80% of the contact surface (Ma et al, 2006).…”
Section: Prediction Of the Ige Binding Sites To The Amino Acid Residumentioning
confidence: 99%